OCT in Glaucoma Diagnosis - Butt, Nadeem Hafeez (Pakistan Journal of Ophthalmology, 2018)
Ocular coherence tomography (OCT) has revolutionized the diagnosis of glaucoma since it was launched as a time domain machine. With advancements in technology fourier domain and swept source machines have been introduced with very high resolution. A higher scan speed of OCT machines (80,000 to 100,000 scan/sec) has made it possible to get a uniform sensitivity over the entire scan window showing both RNFL and lamina cribrosa. World glaucoma association consensus on diagnosis of glaucoma states that clinical diagnosis of glaucoma is predicted on the detection of a thinned retinal nerve fiber layer and narrowed neuroretinal rim which can now be studied in detail with higher resolution machines.